Atividade antibacteriana e composição química dos extratos de Aloysia triphylla (L’Hérit) Britton obtidos por fluído supercrítico (CO2) - Parodi, Thaylise Vey (2010)
The use of natural products is ancient and the importance of these natural resources is being investigated in recent years. Brazil is rich in plant diversity is a rich source of natural products. Fish farming has intensified its production and this contributes to the emergence of diseases. Aeromonas are represented in fish losses due to the pathology they cause and the resistance to antibiotics. Aloysia triphylla is a shrub grown in our region and is used in folk medicine due to different properties, including antimicrobial activity. For methods of extraction using supercritical carbon dioxide is possible to obtain high-purity product, free of solvents and of excellent quality. This study is to evaluate the activity of Aloysia triphylla against Aeromonas sp. based on extracts obtained with supercritical carbon dioxide under different conditions of temperature and pressure, and check the chemical composition of plant material. The results obtained for extracts in the conditions of 30 °C and 100 bar, 70 °C and 200 bar and 50 °C and 150 bar consisted mainly of monoterpenes present as major component E-citral, while for 30 °C and 200 bar predominated limonene. The extract obtained at 70 °C and 100 bar was predominant sesquiterpene caryophyllene oxide and only at 50 °C and 150 bar was detected squalene. The condition of 30 °C and 100 bar showed better activity against Aeromonas sp.. Aloysia triphylla showed bactericidal activity against the genus Aeromonas, but its activity differs from the extraction of condition as a result of the components present.